OSWALD DUCROT'S POLYPHONY THEORY AND TRANSLATION: TRANSLATION ANALYSIS OF LE RACISME EXPLIQUÉ À MA FILLE - Lapúniková, Magdaléna (Bohemica Olomucensia, 2021)
The article discusses the pragmatic level of the translation of the book Le racisme expliqué à ma fille (1999) by the French author Tahar Ben Jelloun. The analysis focuses on the phenomenon of asking question, a significant textual feature of the book hereby examined from the viewpoint of polyphonic theory by the French linguist Oswald Ducrot (1984). The analysis contrasts the source text and its Czech translation by Anna and Erik Lukavští (2004). The aim of the article is to assess the adequacy of the source and the target text with respect to the target child reader. The structure and the terminology of the analysis are inspired by the model of translation criticism by Lance Hewson (2011).
Keywords: children's literature; contrastive pragmatics; functional equivalence; question; translation analysis